Developing technology to enhance learning interpersonal skills in counsellor education. Issue 3 (4th May 2019) - Murphy, David; Slovak, Petr; Thieme, Anja; Jackson, Dan; Olivier, Patrick; Fitzpatrick, Geraldine
ABSTRACT: The integration of new technologies into counsellor education has progressed slowly. We present mPath : an online system designed to support iterative, multi-levelled and deep reflection on practice in skills training sessions. We propose the integration of new technologies to counsellor education as an area with scope for future research and development.